Leviers et obstacles dans les cheminements universitaires à la maîtrise et au doctorat de la population étudiante en situation de handicap émergent (ESHE) - Sall, Mariata; Picard, France; Pilote , Annie (Canadian Journal of Education/Revue canadienne de l'éducation, 2023)
The purpose of this article is to highlight the levers and barriers in the educational pathways and available access to support measures and inclusion of students with emerging disabilities (ESHE) experiencing learning, attention, mental health, and developmental disorders. The study, based on interviews conducted with ESHE master’s and doctoral students, shows that support from key members of the university environment and accompanying services is an important lever in educational pathways and access to accommodations. On the other hand, despite equity, diversity, and inclusion measures, some conditions associated with the measures that are supposed to help sometimes prove to be restrictive or counterproductive (e.g., delays in the disability assessment procedure, non-recognition of a previous disability diagnosis). As a result, ESHEs may be excluded or denied access to support and accommodation services, which limits their academic performance.